Melatonin’s effect on hair follicles in a goat (Capra hircus) animal model - Rong, Youjun; Ma, Rong; Zhang, Yanjun; Guo, Zhenhua (Frontiers in Endocrinology, 2024)
Melatonin can treat androgenetic alopecia in males. Goats can be used as animal models to study melatonin treatment for human alopecia. In this study, a meta-analysis of melatonin’s effects on goat hair follicles was pursued. Literature from the last 20 years was searched in Scopus, Science Direct, Web of Science and PubMed. Melatonin’s effect on goat hair follicles and litter size were performed through a traditional meta-analysis and trial sequential analysis. A network meta-analysis used data from oocyte development to blastocyst. The hair follicle genes regulated by melatonin performed KEGG and PPI. We hypothesized that there are differences in melatonin receptors between different goats, and therefore completed melatonin receptor 1A homology modelling and molecular docking. The results showed that melatonin did not affect goat primary follicle or litter size. However, there was a positive correlation with secondary follicle growth. The goat melatonin receptor 1A SNPs influence melatonin’s functioning. The wild type gene defect MR1 is a very valuable animal model. Future studies should focus on the relationship between goat SNPs and the effect of embedded melatonin. This study will provide theoretical guidance for the cashmere industry and will be informative for human alopecia research.